A Slow Clearing, Fibrin-Specific, PAI-1 Resistant Variant of t-PA (T103N, KHRR 296-299 AAAA) - Paoni, Nicholas F; Keyt, Bruce A; Refino, Canio J; Chow, Alice M; Nguyen, Hung V; Berleau, Lea T; Badillo, Julie; Peña, Luis C; Brady, Kevin; Wurm, Florian M; Ogez, John; Bennett, William F (Thrombosis and Haemostasis, 1993)
Site directed mutagenesis was used to construct a t-PA variant that contains an additional glycosylation site in the first kringle domain (T103N) combined with a tetra-alanine substitution in the protease domain (KHRR 296-299 AAAA). This combination variant has a plasma clearance rate that is 4.5-fold slower in rats and 5.4-fold slower in rabbits than t-PA. It is also less than one tenth as active as t-PA towards plasminogen in the presence of fibrinogen, and has approximately twice the normal activity in the presence of fibrin. It shows substantial resistance to the fast acting inhibitor, plasminogen activator inhibitor-1 (PAI-1), requiring a 10-fold greater molar excess of PAI-1 to reduce its activity by 50%, compared to t-PA. This is the result of a reduction of nearly 100-fold in the second order rate constant for PAI-1 inactivation. These results show that it is possible to combine mutations in different domains of t-PA to construct a variant which is simultaneously slower clearing, less reactive towards plasminogen in the absence of a fibrin clot, and resistant to inactivation by PAI-1.